Delivery room interventions to prevent bronchopulmonary dysplasia in preterm infants: a protocol for a systematic review and network meta-analysis. Issue 8 (18th August 2019) - Mitra, Souvik; Disher, Timothy; Pichler, Gerhard; D'Souza, Brandon; Mccord, Helen; Chayapathi, Varsha; Jones, Karlee; Schmölzer, Georg
Abstract : Introduction: As gestational age decreases, incidence of bronchopulmonary dysplasia (BPD) and chronic lung disease increases. There are many interventions used in the delivery room to prevent acute lung injury and consequently BPD in these patients. The availability of different treatment options often poses a practical challenge to the practicing neonatologist when it comes to making an evidence-based choice as the multitude of pairwise systematic reviews including Cochrane reviews that are currently available only provide a narrow perspective through head-to-head comparisons. Methods and analysis: We will conduct a systematic review of all randomised controlled trials evaluating delivery room interventions within the first golden hour after birth for prevention of BPD. The primary outcome includes BPD. Secondary outcomes include death at 36 weeks of postmenstrual age or before discharge; severe intraventricular haemorrhage (grade 3 or 4 based on the Papile criteria); any air leak syndromes (including pneumothorax or pulmonary interstitial emphysema); retinopathy of prematurity (any stage) and neurodevelopmental impairment at 18–24 months. We will search from their inception to August 2018, the following databases: Medline, EMBASE and Cochrane Central Register of Controlled Trials as well as grey literature resources. Two reviewers will independently screen titles and abstracts, review full texts, extract information and assess the risk of bias and the confidence in the estimate (with Grading of Recommendations Assessment, Development and Evaluation approach). This review will use Bayesian network meta-analysis approach which allows the comparison of the multiple delivery room interventions for prevention of BPD. We will perform a Bayesian network meta-analysis to combine the pooled direct and indirect treatment effect estimates for each outcome, effectiveness and safety of delivery room interventions for prevention of BPD. Ethics and dissemination: The proposed protocol is a network meta-analysis, which has been registered on PROSPERO International prospective register of systematic reviews (CRD42018078648). The results will provide an evidence-based guide to choosing the right sequence of early postnatal interventions that will be associated with the least likelihood of inducing lung injury and BPD in preterm infants. Furthermore, we will identify knowledge gaps and will encourage further research for other therapeutic options. Therefore, its results will be disseminated through peer-reviewed publications and conference presentations. Due to the nature of the design, no ethics approval is necessary.